Development of a non-thermal gliding-arc discharge reactor for biomass tar treatment - Kittikorn Sasujit (2019)
© 2019, Paulus Editora. All rights reserved. Non-thermal plasma technology is an interesting method for removal of tar from gasified biomass. In this study, AC gliding-arc reactors with a reverse vortex flow configuration were developed for biomass tar treatment. Successful generation of plasma discharge was obtained at high volume flows of treated gas. Preliminary experimental results showed that the onset of electric discharge occurred at about 10 kV. A large number of plasma discharges was evident. For our developed prototype, electric power input, total gas feed rate, and various carrier gases (Air, N2, N2+C10H8) were adjusted to investigate their effects on the discharge phenomena. The reverse vortex flow gliding arc discharges showed high residence times for potential chemical reactions inside the reactor. From preliminary tests, maximum removal efficiency of a representative tar compound of more than 93% was found, at an energy utilization efficiency of about 30 g/kWh.